Asymptomatic hearing loss-a missed symptom of COVID-19 - Sathyanarayanan, Choudhary; Swaminathan, Balaji; Shanmugam, Ruta; Shanmugam, V. U.; ., Prakash; Lavanya, V. M.; Divya, P. S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: COVID-19 pandemic is caused by SARS CoV2. The last reference of pandemic was Spanish flu in 1918 which caused hearing loss in many patients. The effect of COVID-19 is an interesting issue in audiology. Not much studies have been done; therefore, this kindled our interest to have a study on audiological profile of asymptomatic COVID-19 patients. Methods: The 20 cases in the age group of 20 and 50 years who were confirmed positive for COVID-19 formed the study group. 20 subjects who had normal hearing (Audiometric threshold at or better than 15 db HL) were used as control group. Pure-tone audiometry (PTA) was done for both the group on day 7 and 30. Air conduction and Bone conduction were measured. The audiometric thresholds were measured using the modified Hughson-Westlake method. Results: High frequency hearing impairment was found in 9 out of 20 patients in the study group on day 7. Out of the 9 affected patients 7 patients showed improvement upon further testing done on day 30. Conclusions: Like anosmia and ageusia, hearing loss can be considered as one of the clinical features in COVID-19 patients. This study was recorded to find a significant hearing loss in asymptomatic COVID-19 patients and thus sheds light on the auditory problem that people are experiencing during these difficult times and for future reference on pandemic research.